2020
DOI: 10.1371/journal.pone.0240231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-inflammatory effects of synthesised tanshinone I and isotanshinone I analogues in zebrafish

Abstract: During inflammation, dysregulated neutrophil behaviour can play a major role in a range of chronic inflammatory diseases, for many of which current treatments are generally ineffective. Recently, specific naturally occurring tanshinones have shown promising anti-inflammatory effects by targeting neutrophils in vivo, yet such tanshinones, and moreover, their isomeric isotanshinone counterparts, are still a largely underexplored class of compounds, both in terms of synthesis and biological effects. To explore th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…We found that 24 h after CLP, the prophylactic treatment with β -Lap was able to reduce neutrophil recruitment. The transgenic zebrafish model was also observed that the β -Lap compound caused reduced recruitment of neutrophils to the injury site, without affecting the resolution of inflammation [ 39 ]. Moreover, it was demonstrated that the topical treatment of Leishmania major -infected BALB/c mice with β -Lap loaded in lecithin-chitosan nanoparticles downregulated IL-1 β and cyclooxygenase (COX-2) in the draining lymph nodes and reduced the cutaneous lesion size and neutrophil infiltration, without affecting parasites burdens [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that 24 h after CLP, the prophylactic treatment with β -Lap was able to reduce neutrophil recruitment. The transgenic zebrafish model was also observed that the β -Lap compound caused reduced recruitment of neutrophils to the injury site, without affecting the resolution of inflammation [ 39 ]. Moreover, it was demonstrated that the topical treatment of Leishmania major -infected BALB/c mice with β -Lap loaded in lecithin-chitosan nanoparticles downregulated IL-1 β and cyclooxygenase (COX-2) in the draining lymph nodes and reduced the cutaneous lesion size and neutrophil infiltration, without affecting parasites burdens [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers ( Jiao et al, 2014 ; Foulkes et al, 2020 ) synthesized tanshinone I using a relatively mild method ( Figure 5 ). Sodium percarbonate was used to oxidize 5-bromovanillin ( 40 ), and the ester functional group was hydrolyzed to obtain 1,4-hydroquinone ( 41 ).…”
Section: Total Synthesis Of Tanshinone Imentioning
confidence: 99%
“…The first modification method of the o-quinone structure of tanshinone I involves the reduction of o -quinone ( 45 ) ( Foulkes et al, 2020 ), followed by acylation of the phenolic hydroxyl group ( 46 ) ( Foulkes et al, 2020 ) or alkylate ( 47 ) ( Foulkes et al, 2020 ). The second modification method uses amine compounds to react with 11 and 12 o-dicarbonyl groups to generate imidazole ( 48 ) ( Li et al, 2018 ), oxazole ( 49 , 50 ) ( Li et al, 2018 ), and pyrazine ( 51 ) ( Li et al, 2018 ).…”
Section: Structural Modification Of Tanshinone Imentioning
confidence: 99%
See 2 more Smart Citations